DESIGN MODELING ASSURE - Anhar Munandar (STAI Pelabuhan Ratu, 2020)
The process of learning and activity can be described as a quality learning and has appeal in being able to motivate students to learn more about the content or subject matter. Model of instructional design ASSURE this is a model of instructional design that is a formulation for the teaching and learning activities (MBC)-oriented class. ASSURE model is the bridge between learners, content, and media. This model is both practical and easy to be implemented in in designing learning activities. In addition, this model is both practical and easy to be implemented in in designing learning activities. In analyzing the characteristics of the students is very easy to determine the methods, media and materials to be used, so that it can create a learning activity that is effective, efficient and engaging.